Existência na paciência: uma Introdução no Pensamento de S. A. Kierkegaard - Germano, Ramon Bolivar Cavalcanti (2014)
In this work we develop a route of approach of to Kierkegaard's work that, taking into account three different moments of his production, allows us a more rigorous and lucid view of his activity as an author and particularly of his way of interpreting the human existence. Bearing in mind the complex nature of the Kierkegaardian corpus accentuated by its indirect form of communication we decided to develop a reading that focused on the meaning that the human existence occupies in the thoughts of the author. Our reading also introduces some of the issues and concepts that form the general understanding framework of human existence as it is understood by Kierkegaard. We show how the existence needs to be understood from a new conception of freedom, as well as from a new understanding of the relationship between being and thinking that is, to be understood as inter-esse which essentially leads to a replacement problem of truth. We conclude with an approach to the problem of becoming yourself or with the question of acquisition of the self (Selv) in patience. With this we approach a more coherent and rigorous comprehension of the interpretation that Kierkegaard makes of human existence particularly taking into account the role that patience takes this reading and by extension, we trace a route of approach of his activity as an author.